Upaya Pelestarian Warisan Budaya Di Pantai Air Manis Kota Padang Sebagai Daya Tarik Wisata Heritage - Annisa Pohan (Institut Seni Indonesia Padangpanjang, 2025)
This study examines how the community and government play a role in preserving the cultural heritage of Air Manis Beach, Padang City, which has two main elements: the Malin Kundang Stone and its folklore. This research is motivated by the declining condition of cultural preservation in the area, where tourism development is prioritized over cultural protection. Using qualitative descriptive methods, data were collected through field observations, interviews with local residents and visitors, and literature studies. Based on field findings, conservation activities in this area are still focused on the development of tourist facilities, while aspects of cultural protection are not optimal. This study reveals that conservation should be carried out in an integrated manner, balancing physical conservation and cultural revitalization. This study contributes to the development of cultural heritage tourism by offering a community-based and educational approach that strengthens local identity and encourages sustainable tourism in Air Manis Beach.